2019
DOI: 10.3390/urbansci3030089
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Sound Environment of Andorra and Escaldes-Engordany by Means of a 3D City Model Platform

Abstract: In the new paradigm of the smart cities world, public opinion is one of the most important issues in the new conception of urban space and its corresponding regulations. The data collection in terms of environmental noise cannot only be related to the value of the equivalent noise level L A e q of the places of interest. According to WHO reports, the different types of noise (traffic, anthropomorphic, industrial, and others) have different effects on citizens; the focus of this study is to use the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The establishment of web-based and real-time noise measurement monitoring systems is also targeted in studies in different countries. For example, Alsina-Pagès et al [ 6 ] stated for the future goals to enable the real-time monitoring of the acoustic environment of the country, the development of real-time operation with a network of acoustic sensors deployed in Andorra and Escaldes-Engordany was aimed. Noise monitoring systems can detail the changes in noise levels over the years and contribute to the determination of urban growth policies.…”
Section: The Strategic Noise Mapping Process Based On Industrial Noisementioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of web-based and real-time noise measurement monitoring systems is also targeted in studies in different countries. For example, Alsina-Pagès et al [ 6 ] stated for the future goals to enable the real-time monitoring of the acoustic environment of the country, the development of real-time operation with a network of acoustic sensors deployed in Andorra and Escaldes-Engordany was aimed. Noise monitoring systems can detail the changes in noise levels over the years and contribute to the determination of urban growth policies.…”
Section: The Strategic Noise Mapping Process Based On Industrial Noisementioning
confidence: 99%
“…Arbaoui et al [ 5 ] reported that noise exposure can cause hearing problems, hypertension, heart disease, and sleep disturbances. Alsina-Pagès et al [ 6 ] stated that in recent years, many researchers aimed at noise reduction to avoid various adverse health effects such as sleep disturbance, discomfort, cardiovascular effects, learning impairment, and hypertension. Bozkurt and Demirkale [ 7 ] stated that environmental noise can significantly affect public health and have a remarkable impact on human activities.…”
Section: Introductionmentioning
confidence: 99%
“…With this idea in mind, some time ago we started a joint project to observe and characterise the different types of noise existing at three specific points in the two cities, with the aim of categorising all the audible sounds at these points into four categories: Traffic, People, City and Works [8]. For this purpose, samples of raw acoustic data were recorded at these locations for two days to be studied and labelled, as well as the final part of visualization of the types of noise [9].…”
Section: Introductionmentioning
confidence: 99%